2023
DOI: 10.1001/jamanetworkopen.2022.56004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Laparoscopic Proximal Gastrectomy With Double-Tract Reconstruction vs Total Gastrectomy on Hemoglobin Level and Vitamin B12 Supplementation in Upper-Third Early Gastric Cancer

Abstract: ImportancePatients undergoing proximal gastrectomy (PG) with double-tract reconstruction (DTR) have been reported to have an incidence of reflux esophagitis that is as low as that observed after total gastrectomy (TG). It is unclear whether PG has an advantage over TG for the treatment of patients with upper early gastric cancer (GC).ObjectiveTo evaluate the effect of laparoscopic PG with DTR (LPG-DTR) vs laparoscopic TG (LTG) on levels of hemoglobin and vitamin B12 supplementation required among patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…Vitamin B12 and iron supplementation were required much less frequently following PG-DTR compared with that following conventional TG. [11,12,22] The present study also demonstrated that the levels of hemoglobin, vitamin B12, and iron were well preserved or recovered from the initial drop during the rst year after surgery. It was an expected result because patients who underwent PG were not deprived of intrinsic factors and gastric acid, which is critical in the absorption of vitamin B12 and iron, thanks to the remnant distal stomach.…”
Section: Discussionsupporting
confidence: 73%
“…Vitamin B12 and iron supplementation were required much less frequently following PG-DTR compared with that following conventional TG. [11,12,22] The present study also demonstrated that the levels of hemoglobin, vitamin B12, and iron were well preserved or recovered from the initial drop during the rst year after surgery. It was an expected result because patients who underwent PG were not deprived of intrinsic factors and gastric acid, which is critical in the absorption of vitamin B12 and iron, thanks to the remnant distal stomach.…”
Section: Discussionsupporting
confidence: 73%
“…35,45 Recently, a randomized controlled trial comparing LPG with DT versus LTG was first reported. 46 Results showed that LPG was superior in reducing vitamin B12 supplementation, but there was no significant difference between LPG and LTG regarding postoperative body weight. In this study, only 60% of the food entered the remnant stomach after DT.…”
Section: Discussionmentioning
confidence: 91%
“…DT has been reported to improve food stagnation at the jejunal interposition; however, its nutritional benefits compared to TG remain unclear 35,45 . Recently, a randomized controlled trial comparing LPG with DT versus LTG was first reported 46 . Results showed that LPG was superior in reducing vitamin B12 supplementation, but there was no significant difference between LPG and LTG regarding postoperative body weight.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the wide application of anastomotic instruments, the attention of perioperative management, and the progress of operation and anesthesia, the incidence of postoperative complications of gastric cancer has decreased signi cantly [21,22].The need for routine placement of abdominal drainage tube after gastric cancer operation for early detection of anastomotic leakage and intra-abdominal bleeding is no longer urgent.According to the results of the relevant prospective randomized controlled study, the intraoperative placement of abdominal drainage tube group did not signi cantly reduce the incidence of postoperative complications such as anastomotic leakage and intraabdominal bleeding [1,13].Therefore, they do not recommend the prophylactic placement of abdominal drainage tube during the operation of gastric cancer.Although the absence of abdominal drainage tube after radical resection of gastric cancer makes clinicians lack an intuitive indicator of postoperative bleeding or anastomotic leakage.…”
Section: Discussionmentioning
confidence: 99%